Pemberdayaan Pemasaran Berbasis Digital UMKM Desa Rancabolang - Pramesti , Puji; Komalasari , Rita; Dwijayanti, Andina; Juliawati , Poniah; Munawar , Zen (IKRA-ITH ABDIMAS, 2024)
Pemberdayaan Pemasaran Berbasis Digital UMKM Desa Rancabolan. Community service activities (PKM) are part of the tridarma that must be carried out by academics, PKM is useful for increasing the relevance of insight through dedication to the community and applying science to have a positive impact on society. PKM activities at LP3I Polytechnic are carried out in several areas, one of which is in Rancabolang Village, Gedebage District, Bandung City. Partners of PKM activities in Rancabolang Village are several MSME Partners Fahmia (British Propolish), Rendang Suwir, Yukusiba (Zuppa Soup), Bandung Jacket Vest, and Catering. As for the results of observations and initial visits to the field, a landing page was found for further explanation of the products sold, MSMEs do not have adequate skills regarding good product photos, and there are MSMEs that do not understand how to manage financial reports. The methodology used is Participatory Action Research (PAR). The results of PKM activities are the creation of digital marketing with heylink.me, landing pages that are inserted into Instagram accounts and the creation of financial data processing using Excel in EXFA format